Challenges in Policy Implementation of Inclusive Quality Education and Sustainable Development Goal #4 in Ethiopian District Primary Schools - Mengistu Debele Gerbi (Ethiopian Journal of Science and Sustainable Development)
Among the 17 Sustainable Development Goals (SDGs) of United Nations, Goal #4 calls for ensuring inclusive and equitable quality education and promoting lifelong learning opportunities for all. However, students with disabilities continue to face exclusionary pressures, especially in developing countries. Achieving SDGs through inclusive education requires more than just declarations of intents; it demands strong commitment to action, ensuring that policies and strategies outlined in national and international frameworks are effectively put into practice. The purpose of this study was to investigate the challenges to achieving inclusive quality education and realizing sustainable development goal #4. Quantitative research design was used, with data collected through questionnaire administered to 219 teachers across six primary schools selected by random sampling. The study examined implementation of inclusive education policy, inclusive leadership, inclusive teaching supports, and availability of educational assistive technologies. The findings revealed that the overall implementation of inclusive education policy (M = 2.56, SD = 1.06), inclusive leadership (M = 2.69, SD = 1.11), availability of assistive technology (M = 2.5, SD = 1.2), and inclusive teaching support (M = 2.80, SD = 1.24) are all low. Moreover, one-way ANOVA revealed that there is no statistically significant differences among schools regarding practice of inclusive education (F (5, 213) = 0.427, p > 0.05). In conclusion, effective implementation of policies and collaboration among all the educational stakeholders is mandatory for inclusive education and to realize SDG #4.